Primary dealers and the demand for government debt - Jason Allen; Jakub Kastl; Milena Wittwer (Bank of Canada, 2020)
Leveraging the fact that in many primary debt issuance markets securities of varying maturities are sold simultaneously, we recover participants' full demand systems by generalizing methods for estimating individual demands from bidding data. The estimated preference parameters allow us to partition primary dealers into two main classes. For the first class, which largely coincides with the largest money market players, we find significant complementarities in their demand for Treasury bills in primary markets, while for the second class, the patterns in their willingness to pay are mixed and time-varying. We present a dealer-client model that captures the interplay between the primary and secondary market to provide a rationale for our findings. We argue that the complementarity likely arises from the large dealers "making markets," and hence requiring to hold inventory of all securities. Our results are useful both for minimizing the cost of financing of government debt and for optimally implementing financial regulation that is based upon partitioning financial institutions according to their downstream business strategies.
Keywords: D44; C14; E58; G12; 330; Debt management; Financial markets